Ergonomics in Caring for People Proceedings of the International Conference on Humanizing Work and Work Environment 2015 - Ray, Gaur G.; Iqbal, Rauf; Ganguli, Anindya K.; Khanzode, Vivek (Springer Nature Singapore : Imprint: Springer, 2018)
This volume comprises the proceedings of the International Conference on Humanizing Work and Work Environment organized by the Indian Society of Ergonomics. The book presents research findings on different areas of ergonomics for developing appropriate tools and work environment considering capabilities and limitations of working people for maximum effectiveness on their performance. The volume is divided into several sections focusing on different ergonomic research activities currently being undertaken at both national and international levels. Considering the high diversity among researchers contributing to this volume, it should prove to be a valuable collection of different approaches that contemporary researchers are adopting on the theme of caring for the people and humanizing work and work environment.  .